Accessibility and Quality Study of Breathing Exercise Applications for Children with Cerebral Palsy (SETITI) - Abdullah, Khabib; Selviyana Dwi Jelita; Fadma Putri (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Cerebral palsy is a chronic condition of movement and posture disorders in children. Children with CP have the potential to experience decreased lung volume due to limited physical activity. So far, breathing exercises have been carried out using conventional media such as whistles, blowing out candles, and the like. A breathing exercise application was created using an Android device called SETITI (sebul tiup-tiup). This application aims to increase children's motivation with modern media, increase practicality in training children with CP to breathe deeply and monitor the results of blowing with numbers that appear on the device screen. The level of accessibility and quality of the application is not yet known so it needs to be researched. This research aims to determine the level of accessibility and quality of the SETITI application. Methods: 17 parents with CP children downloaded the app and tried it on their children. The child is asked to blow into the device's microphone and feedback will appear from the device screen in the form of a moving animation and the sound of applause if the child is successful. After that, parents fill out a questionnaire about the accessibility and quality of the application during use. Results: 100% of parents stated that this application was easy to access and easy to use, had good picture and sound quality, and motivated children to practice breathing. Conclusion: the SETITI breathing exercise application has very easy accessibility, is easy to use, and has good picture and sound quality. It is necessary to increase the choice of screen displays in the form of children's favorite cartoon characters.